Message of Social Criticism on Deforestation in the Lyrics of the Song 'Rat Tua' by FSTVLST - Pendana, Rabil Alberto; Urfan, Noveri Faikar (Universitas Muhammadiyah Tapanuli Selatan, 2024)
The aim of this research is to understand the social criticism message about deforestation in Indonesia through the song